The many faces of the anti-COVID immune response - Vardhana, Santosha A; Wolchok, Jedd D (The Journal of experimental medicine, 2020)
The novel 2019 strain of coronavirus is a source of profound morbidity and mortality worldwide. Compared with recent viral outbreaks, COVID-19 infection has a relatively high mortality rate, the reasons for which are not entirely clear. Furthermore, treatment options for COVID-19 infection are currently limited. In this Perspective, we explore the contributions of the innate and adaptive immune systems to both viral control as well as toxicity during COVID-19 infections and offer suggestions to both understand and therapeutically modulate anti-COVID immunity.